Evaluación del efecto de la adición del hidrogel en el cultivo de Tomate riñón (Solanum lycopersicum) - Cayambe Anrango, Lisseth Estefania (2023)
The depletion of water resources influences the water content needed to meet crop demand. For this reason, it is necessary to take measures or look for alternatives to counteract this problem, since water is the main factor that limits agricultural production throughout the world. The tomato is a crop that requires constant irrigation as well as being one of the most cultivated vegetables in Ecuador. The evaluation of new techniques that allow reducing the application of irrigation is a relevant aspect to study. The main objective of this research was to evaluate the effect of the application of hydrogel on the development and productivity of the kidney tomato crop (Solanum lycopersicum), by incorporating three different doses of this polymer into the soil. The experimental site was the Farm of the School of Agricultural and Environmental Sciences of the Pontifical Catholic University of Ecuador, Ibarra Campus. The methodology consisted of applying 3 doses of hydrogel, a low dose (5g/plant), a medium dose (10g/plant) and a maximum dose (15g/plant). For the experiment, a completely randomized design (DCA) was used, with 4 treatments and 3 repetitions, a total of 12 experimental units, 4 plants per experimental unit, with a total of 48 plants. To control the moisture content, tensiometers placed in the soil in the root zone were used, before and after the application of irrigation. For the calculation of the irrigation sheet, an MC evaporimeter tank was used from which daily evapotranspiration data of the crop were taken weekly and the Kc of the reference crop established by the FAO was used. The benefits of the practice were evident in the variables days to flowering and yield, with T3 being the best treatment (15g dose) that promoted faster flowering and better productivity values. Finally, the moisture content was representative in T3 (15g dose), where it was evident that the hydrogel managed to retain more moisture before and after the application of irrigation\; In addition, the hydrogel reduced the application of water compared to the control. The benefits of the practice were evident in the variables days to flowering and yield, with T3 being the best treatment (15g dose) that promoted faster flowering and better productivity values. Finally, the moisture content was representative in T3 (15g dose), where it was evident that the hydrogel managed to retain more moisture before and after the application of irrigation\; In addition, the hydrogel reduced the application of water compared to the control. The benefits of the practice were evident in the variables days to flowering and yield, with T3 being the best treatment (15g dose) that promoted faster flowering and better productivity values. Finally, the moisture content was representative in 16 T3 (15g dose), where it was evident that the hydrogel managed to retain more moisture before and after the application of irrigation\; In addition, the hydrogel reduced the application of water compared to the control.